Destabilization of peptide: MHC interaction induces IL-2 resistant anergy in diabetogenic T cells - Edwards, Lindsay J. (J Autoimmun, 2013)
Autoreactive T cells are responsible for inducing several autoimmune diseases, including type 1 diabetes. We have developed a strategy to induce unresponsiveness in these cells by destabilizing the peptide:MHC ligand recognized by the T cell receptor. By introducing amino acid substitutions into the immunogenic peptide at residues that bind to the MHC, the half life of the peptide:MHC complex is severely reduced, thereby resulting in abortive T cell activation and anergy. By treating a monoclonal diabetogenic T cell population with an MHC variant peptide, the cells are rendered unresponsive to the wild type ligand, as measured by both proliferation and IL-2 production. Stimulation of T cells with MHC variant peptides results in minimal Erk1/2 phosphorylation or cell division. Variant peptide stimulation effectively initiates a signaling program dominated by sustained tyrosine phosphatase activity, including elevated SHP-1 activity. These negative signaling events result in an anergic phenotype in which the T cells are not competent to signal through the IL-2 receptor, as evidenced by a lack of phospho-Stat5 upregulation and proliferation, despite high expression of the IL-2 receptor. This unique negative signaling profile provides a novel means to shut down the anti-self response.